2022
DOI: 10.3390/ijms231911514
|View full text |Cite
|
Sign up to set email alerts
|

Chemonastic Stalked Glands in the Carnivorous Rainbow Plant Byblis gigantea LINDL. (Byblidaceae, Lamiales)

Abstract: Carnivorous rainbow plants (Byblis, Byblidaceae, Lamiales) possess sticky flypaper traps for the capture, retention, and digestion of prey (mainly small insects). The trapping system is based on a multitude of millimeter-sized glandular trichomes (also termed stalked glands), which produce adhesive glue drops. For over a century, the trapping system of Byblis was considered passive, meaning that no plant movement is involved. Recently, a remarkable discovery was made: the stalked glands of Byblis are indeed ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The insects are likely to die from suffocation due to the clogging of their tracheae. Recently, the long-held theory that the traps of Byblis are nonmotile was first officially disproved by Allan [ 24 ] and further investigated by Poppinga et al [ 28 ] at a cellular level. Through detailed analysis, the authors showed that even though slow in motion, the single-celled stalked trichomes of B. gigantea do react to chemical treatment by moving.…”
Section: Discussionmentioning
confidence: 99%
“…The insects are likely to die from suffocation due to the clogging of their tracheae. Recently, the long-held theory that the traps of Byblis are nonmotile was first officially disproved by Allan [ 24 ] and further investigated by Poppinga et al [ 28 ] at a cellular level. Through detailed analysis, the authors showed that even though slow in motion, the single-celled stalked trichomes of B. gigantea do react to chemical treatment by moving.…”
Section: Discussionmentioning
confidence: 99%